2018
DOI: 10.1002/chem.201801435
|View full text |Cite
|
Sign up to set email alerts
|

A Free Silanide from Nucleophilic Substitution at Silicon(II)

Abstract: A computationally guided synthetic route to a free silanide derived from tris(3‐methylindol‐2‐yl)methane ([(tmim)Si]−) through nucleophilic substitution on the SiII precursor (Idipp)SiCl2 is reported (Idipp=2,3‐dihydro‐1,3‐bis(2,6‐diisopropylphenyl)‐1H‐imidazol‐2‐ylidene). This approach circumvents the need for strained tetrahedral silanes as synthetic intermediates. Computational investigations show that the electron‐donating properties of [(tmim)Si]− are close to those of PMe3. Experimentally, the [(tmim)Si]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…The experimental methods and parameters of the X-ray crystal structure determinations are detailed in the Supporting Information. The compounds (tmim)H 3 , 32 (tmim)Na 3 , 23 (tmim)K 3 , 23 and (tmim)Si – 23 were prepared according to reported procedures.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The experimental methods and parameters of the X-ray crystal structure determinations are detailed in the Supporting Information. The compounds (tmim)H 3 , 32 (tmim)Na 3 , 23 (tmim)K 3 , 23 and (tmim)Si – 23 were prepared according to reported procedures.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Constraining N ‐skatyl moieties into the cage structure B (p K a MP2 =234.5) decreases the sum of N^Si^N angles (Σ N^Si^N ) from 324.7° in A to 311.6° B , while reducing the p K a MP2 by an additional 7.1 units, which is about one fourth of the electron withdrawal contribution. This trend is continued by the more constrained C‐tethered analogue C , which has not been observed experimentally, but its conjugate base has been isolated [17, 44] . With a Σ N^Si^N of 300.5°, its gas‐phase p K a MP2 equals 229.6.…”
Section: Resultsmentioning
confidence: 91%
“…Zwitterionic Si II silanide TSMPSi ( 1 ) was isolated from the reaction of the tris‐indolide salt TSMPK 2 ( 3 ) [16] with Idipp→SiCl 2 used as a Si II source (Scheme 1). [17] The corresponding cationic Si IV silane, [TSMPSiH] + BAr F 4 − ( 2 BARF ), was synthesized by protonation with an equimolar amount of Brookhart's acid (HBAr F 4 ⋅2 Et 2 O). Attempted protonation with HCl led to an intractable mixture of insoluble products, highlighting the importance of a non‐coordinating anion in this reaction (Section S5.1.1).…”
Section: Resultsmentioning
confidence: 99%
“…73 Additionally, we recently showed that the tmim 3– trianion can fully substitute the Si(II) center in (Idipp)SiCl 2 (Idipp = 2,3-dihydro-1,3-bis(2,6-diisopropylphenyl)-1H-imidazol-2-ylidene) to form the naked silanide (tmim)Si – . 33 Scaffold tmimH 3 was synthesized according to the literature procedure, 101 followed by deprotonation using NaH. The reaction of 8 with NEt 4 - 2 was initially conducted in THF at 60 °C.…”
Section: Multidentate N-donorsmentioning
confidence: 99%
“… 32 In this context, silyl ligands bearing electron-withdrawing N-heterocyclic substituents such as N-pyrrolyl or N-indolyl represent an attractive yet underexplored ligand class, with only a handful of representatives known to date. 33 …”
Section: Introductionmentioning
confidence: 99%